Interaction styles in work relationships - Wolf, Denniz B. (University of Wisconsin--Stout, 2019)
Leadership style of supervisors has been heavily researched and supported as an important workplace factor in determining organizational outcomes. However, a follower's perception of a supervisor's interaction style can be equally vital in impacting the dyadic pair's relationship as the supervisor's leadership style. While every individual has his/her own interaction style, understanding another's interaction style offers the potential for improved relationships. This study seeks to further examine the effect that interaction styles have within the dyadic relationships of followers and supervisors by examining how perceived interaction styles between followers and supervisors influence: 1) followers' job satisfaction levels and 2) leadermember exchange (LMX) qualities. A sample of 240 full-time U.S. employees completed a 45- question survey on MTurk about perceptions on current supervisors', preferred supervisors', and own work interaction styles. Hypotheses of the study were explored using four one-way ANOVA tests. Results showed no significant effect between follower-current supervisor interaction style matches/mismatches on followers' job satisfactions but had partial influence over LMX quality ratings. Results revealed partial support for the influence of current-preferred supervisors interaction style matches/mismatches on followers' job satisfactions and LMX qualities.
Keywords: Leadership; Social interaction; Job satisfaction; Supervisors